2009
DOI: 10.1007/s11845-009-0454-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of revision procedures for failed unicondylar knee replacement

Abstract: Results of conversion of UKA to TKA are less satisfactory than primary TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…8 (vs. 19.8 in the primary TKA group) in their study of 63 UKA revisions after 3.1 years mean follow-up. It is also significantly better than Oduwole et al [22], who found a mean WOMAC score of 33.3 in their series.…”
Section: Discussionmentioning
confidence: 49%
“…8 (vs. 19.8 in the primary TKA group) in their study of 63 UKA revisions after 3.1 years mean follow-up. It is also significantly better than Oduwole et al [22], who found a mean WOMAC score of 33.3 in their series.…”
Section: Discussionmentioning
confidence: 49%
“…Revision rates of 6–13% have been reported (Vardi and Strover 2004, Oduwole et al 2009). Oduwole et al (2009) reported that due to possible bone loss, the potential need for augmentations, and use of long-stem prostheses, insertion of a new total knee arthroplasty (TKA) in the proper position can be technically demanding.…”
mentioning
confidence: 99%
“…Revision rates of 6–13% have been reported (Vardi and Strover 2004, Oduwole et al 2009). Oduwole et al (2009) reported that due to possible bone loss, the potential need for augmentations, and use of long-stem prostheses, insertion of a new total knee arthroplasty (TKA) in the proper position can be technically demanding. However, others have found it to be straightforward and less technically demanding than revision TKA (McAuley et al 2001, Dudley et al 2008, Oduwole et al 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations